Ketahanan Psikologis dan Kepuasan Hidup di Era Digital: Studi Integratif tentang Teknologi, Media Sosial, dan Kesejahteraan Mental pada Generasi Z - seno hadi saputro; Ridwan; Kiswanto; Subagiya (Utiliti Project Solution, 2026)
The sharp rise in anxiety and depression among Generation Z following the COVID-19 pandemic underscores an urgent need to understand the factors that protect psychological well-being within digital ecosystems. This study examines the simultaneous roles of psychological resilience, cultural identity, digital literacy, and meaning in life on the psychological well-being and life satisfaction of Generation Z in the Bangka Belitung Islands, Indonesia—a culturally embedded integrative model that has not previously been tested. A sequential mixed-methods design was employed, combining a survey of 250 respondents aged 13–25 analyzed using Structural Equation Modeling (SEM), with 35 semi-structured interviews and 5 focus group discussions analyzed thematically. Psychological resilience was the strongest predictor of well-being (β = 0.48) and life satisfaction (β = 0.42), followed by meaning in life as the most powerful buffer against depression and anxiety (β = −0.52), digital literacy as a reducer of technology-related stress (β = −0.35), and cultural identity as a moderator of social comparison effects (β = −0.24). The four factors operated synergistically: individuals combining high levels of all protective factors showed near-zero anxiety reactivity under high digital stress. These findings call for comprehensive, multidimensional, and culturally responsive digital well-being interventions, particularly in non-Western contexts.